2012
DOI: 10.1093/infdis/jir804
|View full text |Cite
|
Sign up to set email alerts
|

The Prostanoid 15-Deoxy-Δ12,14-Prostaglandin-J2 Reduces Lung Inflammation and Protects Mice Against Lethal Influenza Infection

Abstract: Our results demonstrate for the first time that treatment of mice with 15d-PGJ(2) reduces influenza morbidity and mortality through activation of the PPARγ pathway. PPARγ agonists could thus represent a potential therapeutic avenue for influenza infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 48 publications
8
58
0
Order By: Relevance
“…Recently, our and other research groups have demonstrated the anti-inflammatory activity of exogenously administered 15d-PGJ 2 (12)(13)(14)(15)(16)(17)(18). However, it has been estimated that .50% of the 15d-PGJ 2 added exogenously to a biological system binds to albumin (11).…”
Section: {‖mentioning
confidence: 99%
“…Recently, our and other research groups have demonstrated the anti-inflammatory activity of exogenously administered 15d-PGJ 2 (12)(13)(14)(15)(16)(17)(18). However, it has been estimated that .50% of the 15d-PGJ 2 added exogenously to a biological system binds to albumin (11).…”
Section: {‖mentioning
confidence: 99%
“…PPAR-␥ is a member of the nuclear hormone receptor superfamily of ligand-activated transcription factors. The PPAR-␥ agonist, 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15d-PGJ 2 ), has been shown to reduce inflammatory cytokine and chemokine expression in the lungs of infected mice (9). Therefore, we next evaluated whether this pathway was involved in the increased and persistent inflammatory response in FABP5 Ϫ/Ϫ mice.…”
Section: H1n1-infected Fabp5mentioning
confidence: 99%
“…Influenza virologists usually use either inbred BALB/c or C57Bl/6 mice, 115 and these two strains have been used in all experimental studies of immunomodulatory agents. [84][85][86][87][88][89] These strains might not be optimal for determining which agent might best counteract the more intense inflammatory response in man. For example, in a study of host factors involved in the pathogenesis of pH1N1 virus influenza, BALB/c mice, which have a Th-2 bias, were shown to be less suitable than C57Bl/6 mice, which have a Th-1 bias.…”
Section: Acknowledgmentsmentioning
confidence: 99%